Green Employment Policies and Legal Frameworks in Developing Economies : Towards Sustainable Labor Governance - Dwiprigitningtias, Indah; Trifo Inggiz, Rio; Rakhmania Ardan, R. Ardini; Andayani, Lily; Ikrardini, Zulfika (Intellectual Law Review (ILRE), 2025)
The growing urgency of the global climate crisis compels developing economies to redesign their labor governance systems to integrate environmental sustainability. This study examines the extent to which legal frameworks in developing countries can promote green employment as part of sustainable governance reform. Using a normative juridical approach combined with comparative legal analysis, the research explores statutory provisions and policy instruments from selected countries in Asia, Africa, and Latin America. The data were obtained through legislative interpretation and document review focusing on the convergence between environmental law and labor regulation. The findings reveal that despite strong policy narratives on green growth, the implementation of sustainable labor governance remains fragmented due to weak institutional coordination, limited enforcement, and inadequate legal integration. The study argues that establishing an integrated legal framework linking environmental standards with labor rights is essential to ensure a just transition toward green employment. Such a framework should emphasize coherence, accountability, and cross-sectoral collaboration to achieve inclusive, sustainable economic development.